Prognostic value of platelet to lymphocyte ratio in patients with colorectal cancer undergoing chemotherapy: a systematic review and meta-analysis - Li, Yanfang; Zhou, Juan; Luo, Hui; Li, Shaohua; Shi, Yanru; Chen, Di; Hu, Xuehui (Frontiers in Immunology, 2025)
BackgroundEmerging evidence suggests a correlation between the platelet-to-lymphocyte ratio (PLR) and the prognosis in patients with colorectal cancer (CRC) undergoing chemotherapy. Nevertheless, the existing findings remain contentious.MethodsAn extensive literature review was carried out using PubMed, Embase, Web of Science, and the Cochrane Library up to February 20, 2025, to identify relevant studies on the prognostic role of PLR in clinical outcomes. We applied a set of predefined criteria to determine which studies qualified for inclusion. We assessed overall survival (OS), progression-free survival (PFS), and cancer-specific survival (CSS) using hazard ratios (HR) and corresponding 95% confidence intervals (CI).ResultsOur analysis included nineteen studies (26 comparative groups), involving 4,422 individuals. Aggregate data revealed a significant correlation between PLR values and both OS and PFS in CRC patients receiving chemotherapy (OS: HR = 1.18, 95% CI: 1.03–1.35; p = 0.02; PFS: HR = 1.28, 95% CI: 1.03–1.60; p = 0.03).Specifically, higher PLR values were associated with shorter OS and PFS. This association was observed across varying sample sizes, population characteristics, cut-off values, regions, treatments, and patient ages. However, no significant correlation was found between PLR values and CSS in CRC patients receiving chemotherapy (CSS: HR = 1.27, 95% CI: 0.76–2.10; p = 0.36).ConclusionHigher PLR values are significantly associated with shorter OS and PFS in CRC patients undergoing chemotherapy. However, the analysis did not demonstrate a statistically significant relationship between PLR and CSS in this patient population. In patients with CRC, PLR may serve as a useful marker for predicting outcomes and shaping individualized therapeutic approaches, especially in the context of immunotherapy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251031290.